Compartment Syndrome After Tibial Intramedullary Nail Removal and Intramedullary Debridement: A Case Report. Issue 1 (16th January 2023) - Gong, Davin C.; Patel, Vandan; Farrar, Nicholas; Hake, Mark E.; Perdue, Aaron M.; Ahn, Jaimo
Abstract : Case: A 45-year-old man who sustained an open tibial shaft fracture treated with intramedullary (IM) nailing 9 years earlier presented with persistent pain and concern for occult infection. He underwent tibial nail removal and debridement with reamer-irrigator-aspirator. Postoperative course was complicated by acute compartment syndrome. Conclusion: This is a unique case of postoperative compartment syndrome after IM debridement and tibial hardware removal. A high index of suspicion should be prioritized in patients who complain of severe or unexpected pain to mitigate delays in diagnosis and aid in early treatment.